Application of Advanced Divergent Series Summation Techniques forMolecule Vibrational Energy Spectrum Calculations. Analytical Properties of Complex-valued Energy Function of Different Molecules - Duchko A. N. Andrey Nikolaevich (2015, 2015)
Title screen